Membrane Tethering of SepF, a Membrane Anchor for the Mycobacterium tuberculosis Z-ring. Issue 21 (15th November 2022) - Dey, Souvik; Zhou, Huan-Xiang
Graphical abstract: Highlights: Mycobacterial cell division starts with membrane anchoring of Z-ring by SepF. SepF itself is tethered to membrane by both amphipathic helix and disordered linker. Linker tethering keeps Z-ring at close proximity of membrane. Interactions of late-stage membrane proteins with Z-ring can thereby be formed. Abstract: Bacterial cell division begins with the formation of the Z-ring via polymerization of FtsZ and the localization of Z-ring beneath the inner membrane through membrane anchors. In Mycobacterium tuberculosis ( Mtb ), SepF is one such membrane anchor, but our understanding of the underlying mechanism is very limited. Here we used molecular dynamics simulations to characterize how SepF itself, a water-soluble protein, tethers to acidic membranes that mimic the Mtb inner membrane. In addition to an amphipathic helix (residues 1–12) at the N-terminus, membrane binding also occurs through two stretches of positively charged residues (Arg27-Arg37 and Arg95-Arg107) in the long linker preceding the FtsZ-binding core domain (residues 128–218). The additional interactions via the disordered linker stabilize the membrane tethering of SepF, and keep the core domain of SepF and hence the attached Z-ring close to the membrane. The resulting membrane proximity of the Z-ring in turn enables its interactions with and thus recruitment of two membrane proteins, FtsW and CrgA, at the late stage of cell division.